Becoming noise music style, aesthetics and history - Graham, Stephen 1982- (Bloomsbury Academic, 2023)
"The first book to focus exclusively and comprehensively on the music of noise music, as opposed to contextual questions of politics, history or sociology"--
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Geschichte; Noise; Noise music / History and criticism; Noise rock (Music) / History and criticism; Noise music; Noise rock (Music); Criticism, interpretation, etc